Assessing the Health Risks of Annual Concentrations of Volatile Organic Compounds (VOCs) in Thailand - Laemun, Nuttapong; Kliengchuay, Wissanupong; Srimanus, Wechapraan; Niampradit, Sarima; Aung, Htoo Wai; Limpanont, Yanin; Kiangkoo, Nuttapohn; Mingkwan, Rachaneekorn; Laor, Pussadee; Phonphan, Walaiporn; Niemmanee, Talisa; Suwanmanee, San; Tantrakarnapa, Ph.D, Assoc. Prof. Kraichat (YCAB Publisher, 2025)
Background: Volatile organic compounds (VOCs) are a critical pollutant in Thailand. Children and the elderly are vulnerable to VOCs detected in outdoor environments. Exposure to VOCs might lead to health effects such as sensory irritation, disorders of the nervous system, asthma, and cancer. The volatile organic compound data from twenty-four air permanent monitoring stations covering seven provinces obtained from the Pollution Control Department of Thailand (PCD) showed four out of 9 VOCs to be higher than the criteria level. Objective: This study aimed to assess the quantitative health risk from exposure to four selected VOCs, benzene, 1,3-butadiene, chloroform, and 1,2-dichloroethane, via inhalation. Method: We performed the quantitative health risk assessment for the risk groups, including babies, children, and adults, who lived and worked near air monitoring stations via the inhalation route, following the US Environmental Protection Agency's (EPA) method. We calculated the HQ (hazard quotient) for non-carcinogenic and the inhalation cancer risk for VOCs. Results: The HQ of 1,3-butadiene in Rayong ranged from 0.023 to 4.96 and 0.008 to 1.69 in adults and children, respectively. The calculated HQ was more significant than 1, indicating adverse health effects likely to occur in adults. Whereas the HQ of 1,3-butadiene in other areas is lower than 1, the risk is acceptable. Likewise, the HQ of benzene, chloroform, and 1,2-dichloroethane in all areas is less than 1. The carcinogenic risk assessment of 1,3-butadiene and benzene was 10-6 to 10-4 for both adults and children in Rayong (RY), Khon Kaen (KK), and Bangkok (BKK). Considering the other remaining chemicals, the carcinogenic risks were lower than 10-6 in all areas, which means the cancer risk is negligible. Conclusion: The findings from this study revealed that 1,3-butadiene in ambient air was associated with high non-cancer risk and possible adverse health effects likely to affect human life in Rayong Province. Keywords: VOCs, Health Impact in Thailand, Hazard quotient, non-cancer risk